Współzależności między dochodami a konsumpcją i akumulacją w gospodarstwach indywidualnych - Łuczka-Bakuła, Władysława (Wydział Prawa i Administracji UAM, 1987)
The article considers the problem of reciprocal relations between income on the one hand and consumption and accumulation on the other in private farms keeping business accounts. The analysis reveals that the level of income exerts influence on consumption and accumulation. The level of the latter two competitive values is influenced by the level of income. I particular, the cosumption fund is slower to react to changes of income than the accumulation fund. Generally, the proportions of the distribution of income depend on the hitherto existing level of consumption, the prospects of its increase and the profitability of agricultural production. The level of consumption and accumulation in particular groups of farms is shaped by the forms of intensification. In small farms employing labour- -consuming methods of production the inclination for accumulation is weaker than in larger farms applying capita-consuming methods. Besides, the smallest farms are less immune to crises; in consequence, the crises contribute to a further weakening of their productive activity. In such a situation the differences between the levels of accumulation in the smallest farms and in other groups of farms increase, whereas the respective differences referring to consumption decrease.
Relations between income and consumption/accumulation in private farming